If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + 6 + -7n = 33 + -11n + 29 Reorder the terms: 6 + 3n + -7n = 33 + -11n + 29 Combine like terms: 3n + -7n = -4n 6 + -4n = 33 + -11n + 29 Reorder the terms: 6 + -4n = 33 + 29 + -11n Combine like terms: 33 + 29 = 62 6 + -4n = 62 + -11n Solving 6 + -4n = 62 + -11n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '11n' to each side of the equation. 6 + -4n + 11n = 62 + -11n + 11n Combine like terms: -4n + 11n = 7n 6 + 7n = 62 + -11n + 11n Combine like terms: -11n + 11n = 0 6 + 7n = 62 + 0 6 + 7n = 62 Add '-6' to each side of the equation. 6 + -6 + 7n = 62 + -6 Combine like terms: 6 + -6 = 0 0 + 7n = 62 + -6 7n = 62 + -6 Combine like terms: 62 + -6 = 56 7n = 56 Divide each side by '7'. n = 8 Simplifying n = 8
| 3[1-3x]=2-4x+7 | | 2(2x+4)=48 | | Ln(x+6)-ln(x)=1 | | (5-2i)-(5-6i)= | | -31=3(3x+2)-1 | | -8d-9=-3(1d+3)-5d | | f(x)=-8x^2+7x+6 | | 4(y-5)=5y-20 | | (6+7i)+(5-2i)= | | 3x(x+4)=3x+4 | | 144=-8(7n+5) | | 4x-5=6x^2-7 | | (9x+12)-2(x+3)=6 | | y(17)=0 | | =500+1/5x | | -3(x+9)=-38 | | -10=-4/5y+6 | | =3/20x+1000 | | 5x+13=66 | | 3z+8=z-2 | | In(2x)=5 | | x^3+x^2-(4x+4)=0 | | 7x+34=6x+42 | | 12(2+x)=6 | | 0=-9(-5+r) | | 19-(-1x)=25 | | 17=x-7 | | -3v+8(v+7)=6 | | 2(3x-4)-3=3x-38 | | 16x-4x-2=22 | | -9(5+m)=90 | | -27=-5w+2(w-3) |